2009
DOI: 10.1097/sla.0b013e31819a8b4f
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mortality in Older Trauma Patients Sustaining Injuries from Falls or Motor Vehicle Collisions Treated in Regional Level I Trauma Centers

Abstract: Elderly patients sustaining fall-related injuries and treated at Level I trauma centers are at risk for excess mortality when compared with those injured in MVCs. Effective and efficient methods for treating this population must be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 39 publications
4
66
1
1
Order By: Relevance
“…However, there are additional factors affecting outcome in the elderly (such as gender, mechanism of injury, medications) which are not shown to be relevant in younger adults (34,38,39). In addition, some factors influencing mortality in younger adults (for example physiological derangement) may need to be assessed differently in older people (42).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there are additional factors affecting outcome in the elderly (such as gender, mechanism of injury, medications) which are not shown to be relevant in younger adults (34,38,39). In addition, some factors influencing mortality in younger adults (for example physiological derangement) may need to be assessed differently in older people (42).…”
Section: Resultsmentioning
confidence: 99%
“…However, in this review injury severity and number of injuries were found to be independent predictors of mortality in older trauma patients (6,36,39). This may be due to the relative inability of older patients to compensate for the stresses of injury, and their propensity for multi-organ failure in response to major trauma (36,48).…”
Section: Injury Related Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sampalis et al, compared older falls victims in Canada to those involved in road traffic collisions (RTCs), and found a higher risk&adjusted mortality in those with falls (7), but that study's findings may not be transferable to developing countries. We therefore designed this study to compare older patients with falls to other older trauma patients, in a developing country.…”
Section: Introductionmentioning
confidence: 99%